Is Barthel Index Suitable for Assessing Activities of Daily Living in Patients With Dementia? - Yi, Yayan; Ding, Lin; Wen, Huangliang; Wu, Jialan; Makimoto, Kiyoko; Liao, Xiaoyan (Frontiers in Psychiatry, 2020)
Objectives: To evaluate application of the Barthel Index (BI) in assessing basic activities of daily living (ADL) of patients with dementia using Rasch analysis. Design: A multi-country cross-sectional study. Setting and Participants: Nineteen long-term care facilities located in China, Japan, South Korea, and Thailand. A total of 644 patients with dementia were included. Methods: Unidimensionality, global and item fit, local dependence, person-item targeting, threshold disordering, and differential item functioning (DIF) were examined. Negative correlations between scores for DIF items and Neuropsychiatric Inventory Nursing Home version (NPI-NH) were evaluated. Results: Item reliability (1.0) and person reliability (.88) were acceptable. The Rasch dimension explained 72.9% of the variance (Eigenvalue=27), while the first contrast explained 6.6% (Eigenvalue=2.4). The “mobility” was misfitting to the Rasch model (infit mean square=1.86). The overall difficulty of the BI exceeded patients’ ability (person location=−2.27 logits). The “stairs climbing” and “mobility” showed narrow category thresholds (< 1.4 logits). The location of “controlling bladder” and “toilet use” overlapped. Removing “stairs climbing”, collapsing categories with narrow threshold widths in “mobility”, and combing “controlling bowel” and “controlling bladder” into one item, improved unidimensionality and item fit of the scale. Only three items (“grooming”, “dressing”, and “toilet use”) were free from DIF across countries. The scores for “feeding” were negatively related to scores for “disinhibition” (r = −0.46, P < 0.01), and scores for “controlling bowel” were negatively related to scores for “disinhibition” (r = −0.44, P < 0.01), “agitation” (r = −0.32, P < 0.05), and “aggression” (r = −0.27, P < 0.01) in Japanese samples. Conclusions and Implications: The performance of the BI for assessing patients with dementia might be compromised by misfit items, person-item mistargeting, measurement gaps, redundant items, narrow threshold width, and item bias. Mobility ability might not be helpful for determining capability of basic ADL in the patients. Comparisons of BI scores between countries should be undertaken with caution due to item bias. Neuropsychiatric symptoms might interact with basic ADL abilities of the patients. We will not suggest using the instrument in patients with dementia, without future refining to improve its performance.